Comportamentos de movimento e função executiva em pré-escolares - Bezerra, Thaynã Alves (2022)
Throughout the of day, the human being is in a continuum of movement behaviors: sleep, sedentary behavior (SB), and physical activity (PA) in all its intensities. Analyzing such behaviors in early childhood can provide subsidies to maximize the success of intervention strategies aimed at health gains for this population. Recently research has analyzed the relationship of these behaviors with several health outcomes, among them the executive function (EF). EF is one of the components of cognitive function related to the responses, especially motor, that the individual provides to a new stimulus. When analyzed individually or simultaneously, these behaviors' role on EF seems to be evident in children, adolescents, adults, and the elderly. However, in preschoolers, the results are still scarce and inconclusive. Thus, this study aimed to analyze the associations between movement behaviors and EF in low socioeconomic status preschoolers. For this, 142 preschoolers, between three and five years old, enrolled at the Child Education Reference Centers in the city of João Pessoa, were evaluated. The data collected were: a) PA using an accelerometer; b) SB utilizing an accelerometer; c) screen time through interviews with parents or guardians; d) sleep by face-to-face interview with parents or guardians; e) EF by the Early Years Toolbox battery; f) cardiorespiratory fitness through the 20m Shuttle Run test; g) anthropometric measurements (weight and height); h) sociodemographic data (age, sex, and income) through interviews with parents/guardians. The statistical analyzes used were Machine Learning techniques (Network analysis), structural equation methods using multivariate regressions and compositional analysis. To answer the objectives of this doctoral thesis, five studies were carried out. The studies showed that the EF of children of preschool age was positively associated with moderate to vigorous PA and sleep and negatively with SB at the weekend. It was also observed that the three behaviors together have greater predictive power in the EF than when analyzed in isolation and that theoretical substitution of sleep time and light PA for moderate to vigorous PA can improve the EF of the preschoolers. Regarding the combinations, the results showed that the combined adherence to the PA and sleep behaviors and screen time and sleep, are the most important variables within a system of complex networks for gains in the EF of children in preschool. The results of this doctoral thesis support 12 the hypothesis that a healthy lifestyle, with more time in PA, reduced time in SB, and adequate sleep time are essential for gains in the EF of low-income preschool children, including as a way to mitigate the deleterious effects of environments adverse to the EF at this stage of life. The results also suggest that interventions in this sense should focus on improving adherence combined with recommendations for PA and sleep, in addition to paying special attention to the type of SB performed by the child in different contexts.